Pengaruh Media Video Tutorial Terhadap Kemampuan Menulis Teks Deskripsi Siswa Kelas VII Mtsn 2 Medan Tahun Pembelajaran 2023/2024 - Anzza Fellda Kasvita; Mara Untung Ritonga (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to determine the effect of video tutorial media on the ability to write descriptive text for students in class VII MTsN 2 Medan for the 2023/2024 academic year. The population of this study was all class VII MTsN 2 Medan for the 2023/2024 academic year, consisting of 10 classes with a total of 320 students. The samples taken were classes VII-1 and VII-4, totaling 32 students in each class. The method used is an experimental research method, this will use the "two group post-test design" model. The instrument used is a description test. Hypothesis testing was carried out using the "t" test. Data without using video tutorial media was classified as not meeting the minimum completeness criteria (KKM) with an average value (mean) of 68.21, students' skills in writing descriptive text using video tutorial media were classified as meeting the category. minimum completeness criteria (KKM) with an average value (mean) of 90.75. Next, hypothesis testing shows tcount>ttable with a value with the t stat getting a value of -15.94956082 and t Critical two-tail getting a value of 2.000297822 so it can be concluded that Ho is rejected and Ha is accepted.